Revitalizing Women as Heads of Families in Aceh (Conflict and Post-Conflict Period) - Munawiah Munawiah; Rashidah Binti Mamat; Nor Azlah Sham Binti Rambely; Ernita Dewi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The protracted conflict in Aceh made women feel more suffering, both physically and mentally. Women are the backbone of the family because their husbands are kidnapped, killed, wandering in search of a safe place. Women who are abandoned by their husbands are often faced with negative stigma. The term woman as the head of the family is an effort to change the view of widowed women to be positioned in the position of roles and responsibilities as the head of the family. Women can be independent with support from various parties towards independent and prosperous, just and dignified families. Post-conflict women as heads of families have a role in women's economic empowerment such as women's savings and loans, joining cooperatives of non-governmental organizations and contributing to village development and development.